Um estudo sobre a avaliação da eficácia com ênfase na municipalização da política de segurança pública no município de Manaus-AM - Ferreira, Antonio Carlos Barradas (2018)
The present study aims to analyze the level of the auxiliary participation of the Municipal Guard in the public security policy, in the city of Manaus-AM. This constitutional forecast is a consequence of the federative form of State adopted in Brazil, as a federation of third degreen, endowing the municipality with governmental and administrative autonomy. After the theoretical study, the trend towards the modernization of public administration was observed with the use of management tools, in parallel with the increasing modernization of the control bodies in the inspection of more effective, efficient and effective results through the use of evaluation methods. Thus, the main foundations of the Strategic Situational Planning were adopted to carry out the research, due to the complexity of the theme in the social context, which consisted of the application of structured questionnaires, with scores generated by the Likert scale. And, on the other hand, there was collection of information about the occurrence of crimes, by the Military Police of Amazonas, in the same period and in the same place of application of the research. The questionnaires addressed the multifaceted view of public security, the scope of which was divided into categories and requirements, at their highest level of detail. With the score generated, the indexes were constructed (of feeling of insecurity and confidence of the agents in their performance), which, when correlated with the number of offenses, obeyed the logic of time and space. The criteria for the analysis respected the segregation of the categories and the elaborated questions, as well as the cut in the criminal types, allowing a better understanding of the specific action of the agents. Thus, it was concluded that, within a criterion of effectiveness, the agents of the Municipal Guard are being allocated in a complementary way to the service of the Military Police of Amazonas, in fact.